Novyy vid vooruzheniy zhazhdet zhertvoprinosheniy - Kukryniksy (Плакат СССР (Plakat), 1981)
Western leaders hanging on clothes line being thrashed by USA general, money falling from pockets into baskets labelled 'NATO' Original title: Новый вид вооружений жаждет жертвоприношений PO-0334